2022
DOI: 10.1080/0886022x.2022.2141646
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of neutrophil-to-lymphocyte ratio in brain-dead donors and delayed graft function in kidney transplant recipients

Abstract: Objectives Neutrophil-to-lymphocyte ratio (NLR) is a simple parameter implying the inflammatory status. We aimed to explore the association of brain-dead donor NLR change with delayed graft function (DGF) in kidney transplant recipients. Methods We retrospectively analyzed the data on 102 adult brain-dead donors and their corresponding 199 kidney transplant recipients (2018 − 2021). We calculated ΔNLR by subtracting the NLR before evaluating brain death from the preoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A phase I clinical trial in 18 recipients of cadaveric renal allografts using anti-ICAM-1 monoclonal antibody showed a lower incidence of DGF [ 93 ], whereas enlimomab, another anti-ICAM-1 antibody, failed to reduce DGF incidence, as revealed by a randomized controlled trial [ 94 ]. A recent study showed that dynamic changes in the neutrophil-to-lymphocyte ratio in donors are promising in predicting posttransplant DGF, which can assist in the early recognition and management of renal graft dysfunction [ 95 ].…”
Section: Neutrophils Highly Correlate With Delayed Graft Functionmentioning
confidence: 99%
“…A phase I clinical trial in 18 recipients of cadaveric renal allografts using anti-ICAM-1 monoclonal antibody showed a lower incidence of DGF [ 93 ], whereas enlimomab, another anti-ICAM-1 antibody, failed to reduce DGF incidence, as revealed by a randomized controlled trial [ 94 ]. A recent study showed that dynamic changes in the neutrophil-to-lymphocyte ratio in donors are promising in predicting posttransplant DGF, which can assist in the early recognition and management of renal graft dysfunction [ 95 ].…”
Section: Neutrophils Highly Correlate With Delayed Graft Functionmentioning
confidence: 99%